Dennis Watkins interviewed by James Waites - Watkins, Dennis; Waites, James, 1955-2014. (2005)
Dennis Watkins discusses his early influences and formative experiences; the many aspects of his association with the Opera House, from tour guide to his holding a place on the Board of Trustees for nine years; Jorn Utzon, producing a complete set of working drawings for potential rehabilitation of his abandoned design; work which has been scheduled to go ahead; the state of Australian theatre today.
Recorded during September and October 2005 at Glebe, N.S.W.
Digital master available
Dennis Watkins studied at the University of Sydney along with a group, that has come to dominate the Australian theatre scene. Working in a wide range of capacities, including that of actor, writer, director, commissioning editor, artistic counsel and more. He is the writer of the witty contemporary musicals, 'Stalin the musical', 'Dingo girl' and co-creator of the opera 'The Eighth Wonder', based on the experience of Jorn Utzon and the building of his Sydney Opera House.
Timed summary (20 p.) and uncorrected transcript (typescript, 241 leaves)
Keywords: Watkins, Dennis. -- Interviews; Sydney Opera House -- Anecdotes; Actors -- Australia -- Interviews; Theatrical producers and directors -- Australia -- Interviews; Musicals -- Writing and publishing; Actors; Theatre producers and directors